(untitled) (International Seven Journal of Health Research, 2024)
Introduction: The appendix is an organ in the human body that serves as a reservoir for natural bacteria in the gastrointestinal tract and also has an immunological function that is not so well understood. The acute inflammatory process that can occur in this organ is called acute appendicitis and is the most common surgical emergency worldwide. Objectives: To carry out a literature review on the analysis between open and laparoscopic appendectomy, and to compare how this surgery is performed in Brazil and worldwide. Material and Methods: The methodology used was a literature review. The research was carried out through an electronic search of scientific articles published on the Scielo (Scientific Electronic Library Online) and Lilacs (Latin American Health Sciences Literature) and Pubmed websites. The health terminologies consulted in the Health Sciences Descriptors (DeCS/BIREME) were used to analyze open and laparoscopic appendectomy. Discussion: Appendectomy has largely replaced open surgery as the treatment of choice for diseases of the appendix, especially acute inflammation, as it has effective results and some advantages. Video appendectomy did not gain absolute acceptance as quickly as cholecystectomy, for example, and it is only in the last 10 years that this type of minimally invasive approach has excelled the open approach worldwide. Conclusion: According to the literature, laparoscopy has recently become the most prevalent way of performing appendectomy. Despite this trend, the majority of appendectomies were performed by the open route. This can be explained by logistical, financial or medical team preparation issues. Some studies have shown that the rate of complications after surgery in the laparoscopic group was significantly lower than in the open appendectomy group.